Analisis Kerentanan Ekonomi Dipesisir Barat Kabupaten Aceh Besar - Sopan Sopian; Agustina Arida; Anwar Deli (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
Abstrak. Penelitian ini bertujuan untuk mengetahui tingkat kerentanan ekonomi masyarakat di pesisir barat kabupaten aceh besar. Analisis tingkat kerentanan ekonomi menggunakah skala SEVI yang di peroleh daeri setiap responden sebanyak 97 responden. Parameter yang di gunakan merupakan pendapatan dan kepemilikan asset dari kedua parameter tersebut digunakan untuk menganalisis kerentanan ekonomi di pesisir di 4 kecamatan di pesisir barat Aceh besar. Pada variabel pendapatan terdapat kerentanan rendah 3 desa di Kecamatan Peukan Bada, 2 desa di Kecamatan Lhoknga,dan 1 desa di Kecamatan Leupung. Pada kerentanan sedang terdapat 1 desa di Kecamatan Peukan Bada, 1 desa di Kecamatan Leupung, 1 desa di Kecamatan Lhoong. Pada tingkat kerentanan sangat tinggi terdapat 1 desa di Kecamatan Lhoong. Kerentanan sangat tinggi di sebabkan karena mata pencaharian masyarakat pesisir adalah nelayan maka dari tiu sangat bergantung pada kondidi alam laut. Dan pada variabel kepemilikan asset terdapat kerentanan sangat rendah 2 desa di Kecamatan Peukan Bada, kerentanan rendah terdapat 2 desa di Kecamatan Peukan Bada, 2 desa di Kecamatan Lhoknga,2 desa di Kecamatan Leupung, dan 2 desa di Kecamatan Lhoong. Pada kerentanan sedang terdapat 1 desa di Kecamatan Peukan Bada 1 desa di Kecamatan Lhoknga, 1 desa di Kecamatan Lhoknga, 1 desa di Kecamatan Leupung dan 3 desa di Kecamatan Lhoong. kerentanan tinggi terdapat hanya 1 desa di Kecamatan Leupung. Dan kerentanan sangat tinggi hanya terdapat di 1 desa di Kecamatan Lhoong.Analysis of Economic Vulnerability in the West Coast of Aceh Besar DistrictAbstrak. This study aims to determine the level of economic vulnerability of the people on the west coast of Aceh Besar district. Analysis of the level of economic vulnerability using the SEVI scale obtained from each respondent as many as 97 respondents. The parameters used are income and asset ownership of the two parameters used to analyze economic vulnerability on the coast in 4 sub-districts on the west coast of Aceh Besar. In the income variable, there is a low vulnerability in 3 villages in Peukan Bada District, 2 villages in Lhoknga District, and 1 village in Leupung District. In moderate vulnerability, there are 1 village in Peukan Bada District, 1 village in Leupung District, 1 village in Lhoong District. At a very high level of vulnerability there is 1 village in Lhoong District. Vulnerability is very high because the livelihoods of coastal communities are fishermen, so they are very dependent on marine conditions. And on the asset ownership variable there is a very low vulnerability in 2 villages in Peukan Bada District, low vulnerability there are 2 villages in Peukan Bada District, 2 villages in Lhoknga District, 2 villages in Leupung District, and 2 villages in Lhoong District. At medium vulnerability, there are 1 village in Peukan Bada District, 1 village in Lhoknga District, 1 village in Lhoknga District, 1 village in Leupung District and 3 villages in Lhoong District. there is only 1 village in Leupung District. And very high vulnerability is only found in 1 village in Lhoong District.